Effect of Math Anxiety and Motivation Against Student Mathematical Connections Capabilities - Haerudin Haerudin; Dewi Anjani; Didymus Ibrahi (Program Studi Tadris Matematika IAIN Salatiga, 2021)
This study aims to determine the effect of mathematics anxiety and learning motivation on students' mathematical connection abilities. This research was conducted in SMP Negeri 1 Cikampek class VII 9. In the selection of research samples using the cluster random sampling technique. With the method of Correlational research type of regression, the data used are quantitative data obtained from the inquiry questionnaire and learning motivation and mathematical connection ability test questions. Data processing techniques used in this study are using multiple linear regression. In this study quantitative data processing was performed using IBM SPSS 21.0 software for windows. The results of this study obtained a regression equation (Y=-58,623+0,678X1+0,359X2) which is linear with a determination coefficient of 30.3%, meaning that about 69.7% is explained outside of the regression equation. Thus, it was found that mathematics anxiety and learning motivation significantly influence students' mathematical connection abilities.